UTHM E-Commerce Website - Mohd Adnan, Muhammad Munajatullah; Noraini Ibrahim (Applied Information Technology And Computer Science, 2022)
The students of UTHM currently face a significant gap in selling or buying items required at the university from another university student. It is common that university students are having challenges when finding educational materials that can be bought from students who already have them for a reasonable price. This study aims to provide a solution for eradicating the gap between the student seller and the student buyer of UTHM. Specifically, an online software solution is given where the students can use it to buy and sell its that they need. To identify the definite requirement of the university students, a survey has been carried out among the students. The respondents were randomly chosen and requirements were noted in two main sections named seller and buyer as those two are the two main components of the system. The results clearly showed the hardships that students had to face to find an essential educational supplement in a short amount of time for a reasonable price and the hardships that students had to face to sell an unwanted item that provide them financially. These results suggest that students are more likely to use a new system that is focused on a student audience in order to buy and sell educational items. On this basis, the solution is implemented as on online shopping system focused on students of UTHM.